Hinokitiol Dysregulates Metabolism of Carcinoma Cell Lines and Induces Downregulation of HPV16E6 and E7 Oncogenes and p21 Upregulation in HPV Positive Cell Lines - Sääskilahti Erika; Syrjänen Stina; Loimaranta Vuokko; Louvanto Karolina (MDPI, 2022)
Background: Hinokitiol (beta-thujaplicin), isolated from the wood of Chamaecyparis taiwanensis, has a wide variety of biological properties including anti-inflammatory, anti-microbial, and anti-tumor effects. Therefore, hinokitiol has become a frequent additive in oral and other healthcare products.
Objectives: Our goal was to determine the anti-tumor activity of hinokitiol on human papillomavirus (HPV) positive (n = 3) and negative (n = 2) cell lines derived from cervical or head and neck squamous cell carcinoma (HNSCC) and keratinocyte cell lines (n = 3) transformed spontaneously or with HPV16E6 and E7 oncogenes.
Methods: The cell-lines were exposed to hinokitiol at different concentrations (0-200 mu M) for 24 h. Cell metabolism, proliferation, and the cell cycle distribution were assessed by MTT- and H-3-thymidine incorporation and flow cytometry. Expressions of p21 and on HPV16E6 and E7 oncogenes were assessed by qPCR.
Results: In all carcinoma cell lines, hinokitiol treatment declined the metabolic activity irrespective of the HPV status. This decline was statistically significant, however, only in HPV-positive cell lines CaSki and UD-SCC-2 when exposed to hinokitiol concentrations at 100 and 200 mu M, respectively (p < 0.05). Immortalized cell lines, HMK and HPV-positive IHGK, were more sensitive as a similar metabolic effect was achieved at lower hinokitiol concentrations of 3.1, 6.25, and 50 mu M, respectively. Hinokitiol blocked DNA synthesis of all carcinoma cell lines without evident association with HPV status. G1 cell cycle arrest and p21 upregulation was found in all cell lines after hinokitiol treatment at higher concentration. However, when the p21 results of all HPV-positive cells were pooled together, the increase in p21 expression was statistically significantly higher in HPV-positive than in HPV-negative cell lines (p = 0.03), but only at the highest hinokitiol concentration (200 mu M). In HPV-positive cell lines hinokitiol declined the expression of HPV16E7 and E6 along the increase of p21 expression. The dose-dependent inverse correlation between p21 and E7 was statistically significant in SiHa cells (r = -0.975, p-value = 0.03) and borderline in UD-SCC-2 cells (r = -0.944, p-value = 0.06), in which p21 and E6 were also inversely correlated (r = -0.989).
Conclusions: Our results indicate that hinokitiol might have potential in preventing the progress of immortalized cells toward malignancy and the growth of malignant lesions. Hinokitiol can also influence on the progression of HPV-associated lesions by downregulating the E6 and E7 expression.